Determinants of Return on Assets of Food and Beverage Companies Listed on the Indonesia Stock Exchange - Yunita, Rizki Arvi; Haris, Abdul (Jurusan Akuntansi Politeknik Negeri Ujung Pandang, 2025)
This study aims to analyze the effect of current ratio and total asset turnover on return on assets in food and beverage companies listed on the Indonesia Stock Exchange. Data analysis uses an associative quantitative approach to determine the relationship between two or more variables, using multiple linear regression analysis of 9 company data collected using purposive sampling technique for the observation years 2020-2024. The results found that partially and simultaneously, current ratio and total asset turnover affect return on assets. This study succeeded in finding the determinant of return on assets that increasing the current ratio value also increases the return on assets value because the company has sufficient assets and low risk, as it already has budgeted funds at maturity. Similarly, related to total asset turnover, the more effective the company is in using its assets to generate net sales, indicating the better the performance achieved by the company. Keywords: Return on asset, Current ratio, Total asset turnover